Offshore Oil and Gas Industry Research Funding Models - An opportunity for coordinated, collaborative, industry based research (Executive Summary) - Stothard, Phillip (National Energy Resources Australia, 2017)
Oil and gas research has traditionally been funded via uncoordinated, individual and collective research funding mechanisms. Duplication of research, reduction in financial leveraging opportunities, retention of knowledge, slow research progress and unfilled knowledge gaps can result. Opportunity exists for Australian offshore oil and gas operators, government, small to medium enterprise and research organisations to collaborate to perform coordinated industry research and improve this situation. Collaboration and targeting high impact research topics provides opportunity to undertake more complex industry research, resulting in improved industry knowledge, enabling safe and efficient recovery of offshore oil and gas resources, and a sustainable industry. Benefits can be maximised for all stakeholders. This paper investigates industry research funding models (IRFM) that may provide a sustainable and coordinated offshore oil and gas industry research mechanism. The objective is improved coordination and accelerated research that provides information to support informed regulation and research & development commercialisation. Within the main report, research questions were posed, funding models and mechanisms identified, options considered and conclusions drawn on the relevance of IRFMs to Australian offshore oil and gas and how an IRFM may be introduced to the industry.